What drives students’ intention to take marketing majoring? An empirical investigation of the critical factors - Nor Asiah Omar,; Muhamad Azrin Nazri,; Zaleha Yazid, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia gi, 2016)
The objective of the research is to examine the relationship among intrinsic motivation, variety of career, introductory unit of marketing course and intention to adopt marketing majoring among first-year undergraduate business students in Malaysia. A total 184 questionnaires were collected via convenience sampling from undergraduate students from public and private universities located in Klang valley and Selangor in Malaysia. Regression analysis was applied to access the relationship between the proposed variables. The findings revealed that all three factors namely, intrinsic motivation, variety of career and introductory unit of marketing course were found to have a statistically significant influence on intention to adopt marketing majoring.